Peripheral intravenous catheter related phlebitis and its contributing factors among adult population at KU Teaching Hospital - Singh, R; Bhandary, S; Pun, KD (Kathmandu University Medical Journal, 2009)
Background: Peripheral intravenous catheter-related phlebitis is a common and significant problem in clinical practice. This study was carried out to determine the occurrence of peripheral intravenous catheter related phlebitis and to define the possible factors associated to its development. Materials and methods: Prospective observational study was carried out on 230 clients who were under first time peripheral infusion therapy during two months period: September - October, 2007. Peripheral infusion site was examined for signs of phlebitis once a day. Jackson Standard visual phlebitis scale was used to measure the severity of the phlebitis. SPSS software was used to enter, edit and analyze the data and t-test, chi-square test, binary logistic regression and ROC curve were used to draw the statistical inferences. Results: Phlebitis developed in 136/230 clients (59.1%). It was very mild in most cases. Increased incidence rates of infusion related phlebitis were associated with male sex, small catheter size (20 gauge), insertion at the sites of forearm, IV drug administration and blood product transfusions. The incidence rate of phlebitis rose sharply after 36 hours of catheter insertion. Conclusion: Peripheral Intravenous therapy related phlebitis at KUTH, Dhulikhel Hospital is a significant problem. Related risk factors as found in the present study were insertion site (forearm), size of catheter (20G) and dwell time (>= 36 hours). There were higher incident of phlebitis among the client with Intra venous drug administration and especially between ages 21 - 40 years. Therefore more attention and care are needed in these areas by the care provider. Key words: Phlebitis, Intravenous Therapy, Catheter, Risk Factors, KUTH, Nepal. doi: 10.3126/kumj.v6i4.1732 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 443-447